Stunting-Induced Compensatory Growth in Aquaculture: Mechanisms and Implications - Purayil, Suresh Babu Padinhate; Muralidhar, Ande P.; Syamala, Karthireddy; R, Somu Sunder Lingam (Stunting-Induced Compensatory Growth in Aquaculture: Mechanisms and Implications, 2025)
Compensatory growth (CG) is an elevated growth rate often observed in fish that have previously experienced stress and returned to normal conditions. To induce CG responses, fish must undergo a catabolic phase, where they utilize endogenous energy reserves. In nature, fish encounter catabolic phases due to food limitations, migration and predation. In aquaculture, the catabolic phase is achieved through stunting practices such as feed restrictions, environmental manipulation and crowding stress. When fish experience the catabolic phase in captivity, they undergo various behavioural, physiological and biochemical changes to cope with the altered environmental conditions. Behavioural changes include reduced swimming and locomotion activities. Physiological adjustments involve metabolic changes such as reduced circulation of proteins, antibodies, enzymes and other molecular compounds. In biochemical alterations, fish utilize endogenous energy resources, such as lipids and proteins, which affect their overall nutritional composition. However, when stressed fish return to favourable conditions, they exhibit a CG response and rapidly restore their lost body weight, metabolic compounds and endogenous energy reserves. The effectiveness of the CG response can vary significantly depending on several factors, including the specific fish species, duration and severity of the stunting practice, as well as the conditions during the refeeding phase. This phenomenon has been harnessed in aquaculture to produce stunted fish seed. Extensive research on CG responses in fish over the past few decades has yielded inconsistent results, fostering debate over the practical application of CG response in aquaculture. To better understand and potentially leverage this phenomenon in aquaculture practices, it is crucial to critically examine the physiological changes that occur in fish during both stunting and post-stunting phases. This book aims to provide a comprehensive analysis of the actual changes occurring in fish during the stunting and post-stunting phases and explore the potential applications of CG responses in aquaculture, offering insights for more efficient and sustainable fish farming practices.